Social interactions of Sand Miners in Laosu Village, Bondoala Sub District, Konawe District - Salahuddin, Salahuddin; Daud, L; Sulmiyatin, Sulmiyatin (Jurnal Ilmiah Membangun Desa dan Pertanian, 2020)
This study aimed to determine the social interaction of sand miners in the Laosu Village Bondoala Sub District Konawe District. The research sample consisted of 15 sand miners. The descriptive analysis was used to conduct this research—descriptive techniques for social interaction of sand miners in cooperation and competition, using the interval formula. This study indicated that social interaction with sand miners in collaboration and mutual help from fellow miners knew that the sand is the high category. At the same time, social interaction with sand miners in terms of individual competition and competition for the position and the role of the sand miners fall into the low category. Then social interaction sand miners in the form of a personal conflict of sand miners and social class antagonism sand miners in the deficient category.